Diary of a wimpy kid. The long haul [videorecording (DVD)] - Bowers, David, 1970-; Drucker, Jason, 2005-; Silverstone, Alicia; Scott, Tom Everett, 1970-; Walters, Wyatt; Kinney, Jeff (Twentieth Century Fox Home Entertainment, 2017)
Greg schemes to use his family trip to Meemaw's 90th birthday party as an opportunity to sneak into a video game convention.